Resilience of Vocational High School Students from Divorced Families: Facing Challenges and Navigating Career Choices - Puspitasari, Desty Ratih; Nurhadi, Didik; Yoto, Yoto (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study aims to investigate the resilience of vocational high school students from divorced families as they encounter life challenges and make career decisions. Employing a qualitative intrinsic case study approach, the research involved students from divorced families as the main participants. Data were collected through in-depth interviews with participants and their significant others, supported by document analysis, and analyzed using a thematic analysis approach. The results reveal five key themes: parental divorce, coping dynamics, sources of resilience, career choices, and factors influencing career decisions. The findings indicate that resilience is influenced by emotional regulation, stress-coping strategies, attachment figures, self-control, gratitude, and optimism dimensions that correspond to the concepts of "I am," "I have," and "I can." Career choices, meanwhile, are influenced by family heritage, childhood experiences, parenting patterns, and personal needs. This study provides a novel contribution by integrating resilience theory with career development perspectives in vocational education contexts, particularly among students affected by parental divorce. The results highlight the importance of resilience as a predictor of adaptive capacity in career decision-making. The implications suggest that educators, counselors, and schools should design targeted intervention programs to strengthen resilience and facilitate career readiness among students from divorced families.